The associations between body dissatisfaction, exercise intensity, sleep quality, and depression in university students in southern China - Hao, Ming; Liu, Xuesheng; Wang, Ying; Wu, Qingfeng; Yan, Wenjing; Hao, Yanbin (Frontiers in Psychiatry, 2023)
Background In recent years, depression in early adulthood has become an urgent global public health concern. The university years mark a transitional period from adolescence to adulthood. Young people are required to face academic and life pressures independently, which increases the risk of mental health problems in university. Purpose The main goal of the current study was to explore the sex differences in depression, body dissatisfaction, sleep quality, and exercise intensity among university students in southern China and to analyze the factors affecting the level of depression among university students. Methods In total, 1,258 university students aged 18–23 years were recruited for this study. All participants completed anthropometric measurements, the Self-rating Depression Scale, Physical Activity Rating Scale, and Pittsburgh Sleep Quality Index. Body dissatisfaction levels were measured using sex-appropriate silhouettes. Results Compared with young women, young men had higher exercise intensity and sleep quality, whereas young women’s body dissatisfaction and depression levels were significantly higher than those of young men. Sleep quality score (β = 0.34, p < 0.01), sex (β = 0.15, p < 0.01), physical activity score (β = −0.14, p < 0.01), and body dissatisfaction (β = 0.14, p < 0.01) were significant predictive factors of the Self-rating Depression Scale score. Conclusion Low levels of physical dissatisfaction have a positive effect on depression, and high levels of physical activity and quality sleep can also improve depressive symptoms. At the same time, increasing body satisfaction has the effect of increasing physical activity and improving sleep quality. Therefore, there is great potential to prevent and ameliorate depression by reducing body dissatisfaction.